Associations between physical activity domains and oral health: an analysis of a Brazilian population-based study - Stefany Duarte dos ANJOS; Rafael Milani FERRO; Bernardo Novak LASKAWSKI; Alex Nogueira HAAS; Rodolfo Coelho PRATES; Joao Paulo STEFFENS (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Physical activity comprises four domains (leisure, transportation, domestic, and work activities) that may be differently associated with oral health. The aim of this study was to assess the association between each physical activity domain and oral health conditions in Brazilian adults. A total of 38,539 participants in the 2019 Brazilian Health Survey aged 30 years or older were analyzed. The outcomes were self-perceived oral health (dichotomous) and self-reported number of missing teeth (counts). The presence, frequency, and time of activity in each domain and their combination were analyzed as main exposures. Odds ratios (OR) and mean ratios (MR) were estimated by fitting multivariable models. Higher leisure time physical activity was the only domain associated with better self-perception of oral health (OR = 1.32; 95%CI 1.26-1.38) and lower tooth loss (MR=0.88; 95%CI 0.86-0.90). Higher levels of work, transportation, and household activities were significantly associated with worse self-perception of oral health, while higher levels of work- and transportation-related physical activities were also associated with greater tooth loss. When the total recommended weekly physical activity time was analyzed, no significant associations were found. Sensitivity analysis suggested that this pattern persists in potential periodontitis-related cases, such as when selecting older age or excluding individuals with no tooth loss. In conclusion, leisure physical activity was the only domain with the potential of reflecting the benefits of physical activity on oral health. The inclusion of other domains can confound this association.